A Discordant Monozygotic-Twin Approach to Potential Risk Factors for Chronic Widespread Pain in Females. (2nd March 2015) - Burri, Andrea; Lachance, Genevieve; Williams, Frances
Abstract : Chronic widespread pain (CWP) is a common disorder affecting up to 15% of the general population. The objective of the present study was to explore the role of previously reported psychosocial and interpersonal risk factors on variation in CWP by investigating CWP discordant monozygotic (MZ) twins. This approach allows separation of cause and effect relationships, albeit imperfectly, as well the control for critical confounding variables such as common environment or genetics. In a total sample of N = 3, 266 female twins aged 18–89 years, MZ (113 full pairs) and DZ twins (180 full pairs) discordant for CWP were selected. Items from the London fibromyalgia symptom screening questionnaire were used to discriminate cases from controls. To assess potential risk factors, including body mass index, anxiety sensitivity (AS), emotional intelligence, personality, obsessive-compulsive behavior, and coping, validated questionnaires were used. A set of univariate and multivariate logistic regression analyses were conducted. Of the variables showing significant links with CWP in the univariate individual-level analyses, including age, AS, and emotional intelligence, only emotional intelligence turned out to an independent predictor to the pathogenesis of CWP in both the individual level and discordant MZ analyses. These data indicate that in women having identical genetic risk, emotional intelligence seems to play a key role, although of small effect, in the development and/or maintenance of CWP. It further seems that many of the previously reported risk factors for CWP suffer from genetic confounding.